Influence of asphalt on fatigue crack monitoring in steel bridge decks using guided waves. (1st September 2016) - Pahlavan, Lotfollah; Mota, Mariana M.; Blacquière, Gerrit
Highlights: The role of asphalt in guided-wave propagation in steel deck plates is disclosed. The temperature-dependent behavior of asphalt is incorporated in the analysis. A good correlation between the numerical and experimental results is demonstrated. The effect of asphalt on the accuracy of a crack sizing methodology is quantified. The extent of the effect of asphalt in the system depends on its type/composition. Abstract: Asphalt materials generally exhibit temperature-dependent properties, which can influence the performance of fatigue crack inspection and monitoring systems for bridge deck structures. For a non-intrusive fatigue crack sizing methodology applied to steel decks using ultrasonic guided waves, the effect of asphalt has been investigated. A higher-order spectral finite element model has been implemented to capture the propagation characteristics of guided waves in the multi-layer waveguide. Experimental evaluation has been performed on an aluminum plate covered with bitumen. The results reveal that the extent of the effect of asphalt on propagation of guided waves depends on the type and layout of the asphalt. For a particular asphalt type of interest, i.e. open asphalt surfacing, however, this effect appeared to have limited influence on the performance of the crack sizing methodology, i.e. in the order of a few percents. In the analysis, temperature variation, and uncertainties in the material properties and asphalt bonding condition have been taken into account.